THE EFFICACY OF INTRAARTICULAR TENOXICAM IN THE TREATMENT OF KNEE OSTEOARTHRITIS - Deniz Evcik; Burçak Kızılay; Gökhan Maralcan (Archives of Rheumatology, 2001)
Knee osteoarthritis is a degenerative disorder that can cause pain and limitation. In the treatment intraarticular injections are very popular in recent years. In this study we investigated the efficacy of intraarticular tenoxicam injections in knee osteoarthritis. Fifty patients with knee osteoarthritis were included the study and they were randomly assigned in two groups. Oral paracetamol, hot-pack and exercise therapy were applied both groups. Additionally patients in group 1, had intraarticular tenoxicam injection. Patients were evaluated for pain and fuctional capacity. Pain was assessed by Visual Analog Scale (VAS) and functional capacity was assessed by Lequesne Ð Samson index. After one month there were statistically significant improvement in both parameters in patients treated with intraarticular tenoxicam injections (p<0.001). Finally we think that tenoxicam which is a nonsteroidal antiinflamatory drug used orally in the treatment of osteoarthritis, seems to be effective in intraarticular form as well.